Loyalty of Domestic Tourists to Beach Tourism: Role of Image, Experiential, Digital Marketing and Satisfaction - Juhari, Juhari (Integrated Journal of Business and Economics (IJBE), 2023)
ABSTRACT This study aims to explain the effect of destination image, experiential marketing, and digital marketing communications on tourist satisfaction and the implications for domestic tourist loyalty to beach tourism objects on Bangka Island. This research is quantitative research with descriptive and verification methods. The study's sample consisted of 305 domestic tourist respondents who visited beach tourism objects on Bangka Island using a proportional random sampling technique, and sample size using maximum likelihood estimation. A questionnaire was used to obtain the data and a causality approach was analyzed using Structural Equation Modeling (SEM), using Lisrel 8.8. The results of the study show that the image of the destination, experiential marketing, and digital marketing communications have a positive and significant effect on tourist satisfaction with an R2 value of 63%, and destination image, experiential marketing, digital marketing communications, and tourist satisfaction together have a positive and significant effect on domestic tourist loyalty to beach tourism objects in Bangka Island with an R2 value of 54%. The results of this study prove that the tourist satisfaction variable is an intervening variable that has a positive full mediating effect on destination image, experiential marketing, and digital marketing communications on domestic tourist loyalty to beach tourism objects on Bangka Island. Keywords: Destination Image, Experiential Marketing, Digital Marketing Communication, Tourist Satisfaction, and Tourist Loyalty.